Evolution of Cyclostome Hox Clusters - Pascual-Anaya, Juan; Böhmer, Christine (CRC Press (Taylor & Francis Group, LLC), 2023)
Hagfish and lampreys represent the only two lineages of agnathan (jawless) vertebrates that have survived to the present day, and both form the monophyletic group of cyclostomes, which is sister to the rest of the vertebrates, the gnathostomes (jawed vertebrates). Comparisons between cyclostome and gnathostome models are thus essential to infer and understand ancestral traits of vertebrates and their subsequent morphological, genomic, and physiological evolution. It is thought that Hox gene evolution had a major impact in vertebrate morphological diversification, but it has not been until the last decade or so that significant knowledge on the organization and regulation of the Hox clusters of cyclostomes has started to accumulate. In this chapter, we review current data on cyclostome Hox biology, presenting an integrated view of what we know thus far from studies of Hox genes of both the lamprey and hagfish, including their gene complements, cluster evolution, functional and expression diversification, and how this all relates to their body plans and the general vertebrate architecture. We present the similarities and differences with the most well-known gnathostome Hox genes, and infer common, ancestral traits. In conclusion, we propose a common ancestor radically different to previous reconstructions, with only two Hox clusters instead of four, but in which most of the well-known traits of Hox genes –spatial and temporal collinearity, association with cranial segmentation and posterior growth— were already established. This relatively simpler two-cluster ancestor was then independently modified in the cyclostome and gnathostome lineages, where although Hox characteristics have been broadly retained, lineage-specific differences arose over hundreds of millions of years of independent evolution, which could be behind the morphological diversification of each of the groups.
Keywords: Vertebrados - Evolución; Hox genes; cyclostomes; vertebrate evolution